The Interplay of Interest between Indonesia and Sweden in Blue Economy Cooperation - Oktaviani, Jusmalia; Muhamad Iqbal, Firdaus (Nation State: Journal of International Studies, 2023)
In the beginning of 1950’s, Indonesia and Sweden have maintained diplomatic relations for the past 72 years. Multiple areas of collaboration have been implemented by both parties. Collaboration based on a blue economy is one of the initiatives implemented to foster economic progress. This study seeks to assess how Indonesia's national interests align with those of Sweden in the blue economy. To solve this research question, the research used the Neoliberalism of international cooperation and national interests. The blue economy cooperation agreement between Indonesia and Sweden is listed in the Sweden-Indonesia Sustainability Partnership (SISP). Indonesia should collaborate with Sweden on the blue economy due to the country's competitive advantages in the maritime technology sector. The pursuit of each country's respective goals is the driving force behind the partnership that exists between Indonesia and Sweden. The improvement of the standard of living of the local population as well as the preservation of the marine ecosystem are two of the primary reasons why Indonesia and Sweden should work together to advance the blue economy.